KEMAMPUAN MERUMUSKAN SOAL BAGI MAHASISWA CALON GURU (Penelitian di Program Studi Pendidikan Kimia FTK UIN Ar-Raniry) - Azhar, Azhar (Lantanida Journal, 2014)
On learning activities, there are several processes, one of which is the implementation of the evaluation. To carry out its own evaluation of learning requires the ability to formulate an instrument for the evaluation. Every teacher should have the ability to formulate questions correctly so that the matter will be communicative, with complete data and can be understood by students. Student and Teaching Faculty Tarbiyah UIN Ar-Raniry as a prospective teacher must also be known ability to formulate a matter before the respective assigned in the field. The purpose of this study is to determine the ability to formulate questions for student teachers in the Department of Chemistry, Faculty of Education and Teaching UIN Tarbiyah Ar-Raniry. In general the results of this study are expected to be useful as reference material for the development of the evaluation process of learning, and in particular the issue of the ability to formulate questions for student teachers. This study uses research design evaluation (evaluation research). Data collected through tests and interviews. Data obtained from this study were processed using analytical techniques to the test result by means of the formulation of questions students are classified by the type of formulation of the problem. The results of this classification is an indicator of students' ability to formulate / create questions. The tests will be carried out in stages (four times the test) the situation of different tasks according to four subpokok discussion in learning Chemistry Calculation. From the test results the ability to formulate questions can be seen that in the stages of an increase in students' ability to formulate problems / questions that are appropriate to the situation of a given task. Comparison of the ability to formulate a matter of student learning Chemistry in the calculation of the stages can be described as follows: stage-4> stage-3> stage-2> stage-1. Comparison of the ability to formulate a matter of students in stages at each learning subpokok discussion of material Calculation Chemistry there are no significant differences, except for differences in the ability to formulate a matter between the phase-1 to phase-2, this is due to the learning stage-1 students are still in the process of adapting the pattern formulate questions, and students are still in a state of hesitation to formulate questions because they think that is the task of formulating a matter of lecturers / teachers are confidential, and they should not be involved in the formulation / formation of the matter. Cognitive processes used by the student in formulating (forming) problems is through the association, which is a process of hooking something to others.